ANALISA STRUKTUR BANGUNAN DENGAN KOLOM TIDAK MENERUS - Tungadi , Reonaldo; Tanijaya, Jonie; Kalangi, Hendry Tanoto (Jurnal Media Teknik Sipil, 2024)
Discontinuous column is a column that doesn’t transfer the load directly to the foundation. The use of non-continuous columns includes irregular buildings because the location of the columns is not continuous so that the capacity of the columns is not vertically adjacent, and the result is that the load is quite large on the beams under the column. To carry the non-continuous column load, the beam is designed as a transfer beam, where the beam must be able to withstand the load above it, namely in the form of the beam's weight, gravity loads, earthquake loads, and also the column loads above it, then the loads that are carried will be transferred evenly to the two columns that carry the transfer beam. This study aims to determine the effect of non-continuous columns on the building structure and to determine the difference in concrete volume and reinforcement area that occurs. This research used 2 building models. The results showed that there was an increase in the volume of concrete in the non-continuous column by 13.088% for the column structure, 56.399% for the beam structure. For beam reinforcement area with dimensions of 25cm x 45cm, there was an increase of 59.029% for support reinforcement and 27.007% for field reinforcement. The 20cm x 30cm beam has an increase of 33.6% in support reinforcement and 46.2% in field reinforcement.